2015
DOI: 10.4238/2015.march.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial diversity and niche in rhizosphere soil of healthy and diseased cotton at the flowering stage in southern Xinjiang

Abstract: ABSTRACT. Understanding how microbial community composition and diversity respond to continuous cropping obstacle is not well understood. However, determining the community composition vs assessing the diversity of molecular operational taxonomic units is often difficult. In this study, we focused on the microbial diversity and niche differentiation in rhizosphere soils between healthy and diseased cotton using a molecular approach based on a culture-independent method. A total of 124 operational taxonomic uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The soil bacterial and fungal communities of healthy soils were very different from the bacterial wilt infected soils. We also found the healthy soils had higher microbial diversity, as reported, the soil microbial diversity is positively correlated with the plant resistance to pathogens 2426 . Healthy soils had higher abundances of beneficial microbes ( e .…”
Section: Discussionsupporting
confidence: 86%
“…The soil bacterial and fungal communities of healthy soils were very different from the bacterial wilt infected soils. We also found the healthy soils had higher microbial diversity, as reported, the soil microbial diversity is positively correlated with the plant resistance to pathogens 2426 . Healthy soils had higher abundances of beneficial microbes ( e .…”
Section: Discussionsupporting
confidence: 86%
“…The relationship between the bacterial community structure of cauliflower‐cultivated soils and the occurrence of clubroot has not yet been addressed, although it is known that microbial diversity is positively correlated with the suppression of disease (Bailey & Lazarovits, 2003; Hadar and Papadopoulou et al, 2012; Luan et al., 2015; Liu et al., 2016; Wang et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to a recent report that the microbial community diversity was higher in soils with healthy plants than in soils with plants infected by bacterial wilt ( Wang et al, 2017 ). It has also been reported that the rhizosphere soil microbial community diversity is positively correlated with plant health ( Bulluck and Ristaino, 2002 ; Luan et al, 2015 ). The results suggest that a highly diverse soil microbiome (greater numbers of microbial species) would decrease the chances of bacterial wilt outbreak.…”
Section: Discussionmentioning
confidence: 97%